Glass ceramic and display glass cover plate

By etching the microcrystalline glass substrate with etching liquid, a moth-like structure is formed, which solves the problems of complex process, high cost and insufficient penetration effect in the prior art, and achieves the preparation of microcrystalline glass with high transmittance.

CN119430669APending Publication Date: 2025-02-14CHONGQING AUREAVIA HI TECH GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411582468.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the preparation process of moth-like structure glass is complex, the structure is prone to failure, the production cost is high, it is not conducive to large-scale production, and the penetration enhancement effect is insufficient.

Method used

By surface etching treatment on the main surface of the microcrystalline glass substrate using an etching solution, a microcrystalline glass having a moth-like structure is formed. The specific composition of the etching solution includes 0.01% to 16.00% acid solution, 0% to 18.00% additives and The balance is a component of water.

Benefits of technology

The production of microcrystalline glass with moth-eye-like structure is achieved with a simple process and low cost, which improves its transmittance in the visible light range, reaching more than 91.00%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430669A_ABST
    Figure CN119430669A_ABST
Patent Text Reader

Abstract

The invention discloses a display glass cover plate, which is characterized in that the display glass cover plate comprises microcrystalline glass, the microcrystalline glass comprises a microcrystalline glass substrate and a plurality of nano-scale bulge structures arranged on the main surface of the microcrystalline glass substrate, and the plurality of nano-scale bulge structures and the microcrystalline glass substrate are integrated. The nanoscale protruding structures are crystal substances of glass ceramics, and main crystal phases of the glass ceramics substrate comprise petalite and lithium silicate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of glass technology, and specifically to a microcrystalline glass and a display glass cover. This invention patent application is a divisional application of an invention patent application with an application date of February 24, 2023, an application number of 202310164166.6, and an invention name of "a microcrystalline glass with a moth-eye-like structure and a preparation method thereof". Background Art

[0002] Glass serves as an external protective barrier for many optical devices and equipment. It can effectively prevent direct contact with water and other harmful substances that may damage instruments and equipment. It also serves as a transparent window for light propagation, providing visual effects. However, due to the different refractive indexes of glass and air for light, Fresnel reflection will occur at the interface between glass and air, affecting the transmittance of light in the glass.

[0003] The study found that the regular and orderly nano-subwave structure can form a smooth gradient refractive index at the interface of two different media, thereby effectively suppressing the Fresnel reflection phenomenon and achieving the effect of anti-reflection and anti-transmission. Inspired by biology, the moth eye structure is used in glass surface modification because of its broadband anti-reflection and anti-transmission effect, thereby solving the problem of light transmittance in glass being affected by Fresnel reflection. Studies have shown that the moth eye is a compound eye structure, and its surface is covered with a layer of raised structure, which can cause the irradiated light to diffusely reflect in different directions. According to optical theory analysis, the raised structure on the surface of the moth eye is equivalent to the surface refractive index gradually changing downward along the surface of the material, which effectively solves the reflection phenomenon caused by the sudden change caused by the different refractive indices of light in the air and the material.

[0004] Regarding the preparation of bionic moth-eye / moth-eye-like micro-nano structures on glass surfaces, the existing methods mainly include wet etching technology and nanoimprinting technology. The anti-reflection effect of moth-eye-like structure glass obtained by these methods is generally not ideal, and it is difficult to ensure the acquisition of bionic moth-eye structure glass / moth-eye-like structure glass with high transmittance. Moreover, most of these methods have the disadvantages of being difficult to control or high cost. For example, nanoimprinting technology requires the assistance of photoresist, and it is also necessary to transfer the micro-nano structure on the template to the glass surface. The preparation process is complicated and the production cost is high. Moreover, due to the different materials of the micro-nano structure and the glass material, the micro-nano structure is easy to fall off during use, resulting in the failure of the moth-eye-like structure. In wet etching technology, in order to achieve controllable manufacturing of moth-eye micro-nano structures, technicians usually choose to mask the glass surface to form a regular distribution of metal ions on the glass surface, and then use the acid resistance of metal ions to achieve selective etching during the etching process, so as to finally form a regular moth-eye micro-nano structure on the glass surface. However, such a preparation process is also relatively complicated, the production cost is high, and it is not conducive to large-scale production. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a microcrystalline glass and a display glass cover to solve the technical problems in the prior art such as complex preparation process of moth-eye structure glass, easy failure of moth-eye structure, high production cost, unfavorable large-scale production and insufficient anti-reflection effect.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] In the first aspect, the present invention provides a microcrystalline glass with a moth-eye-like structure, comprising a microcrystalline glass substrate and a moth-eye-like structure layer arranged on the main surface of the microcrystalline glass substrate, and the moth-eye-like structure layer and the microcrystalline glass substrate are integrally formed; the moth-eye-like structure layer comprises a plurality of nanoscale protrusion structures.

[0008] The present invention provides a microcrystalline glass with a moth-eye structure. The moth-eye structure layer is obtained by etching the main surface of a microcrystalline glass substrate with an etching solution.

[0009] The present invention provides a glass-ceramic with a moth-eye-like structure, wherein the glass-ceramic with a moth-eye-like structure has a moth-eye-like structure layer on two main surfaces.

[0010] The present invention provides a microcrystalline glass with a moth-eye structure, wherein the main crystalline phase of the microcrystalline glass substrate includes petalite and lithium silicate; preferably, the main crystalline phase includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate.

[0011] The microcrystalline glass with a moth-eye structure provided by the present invention has a crystallinity of greater than or equal to 30.00wt%, preferably greater than or equal to 35.00wt%, further preferably greater than or equal to 40.00wt%, preferably 35.00wt% to 95.00wt%, preferably 40.00wt% to 95.00wt%, preferably 50.00wt% to 95.00wt%, and more preferably 60.00 to 95.00wt%.

[0012] The microcrystalline glass with a moth-eye structure provided by the present invention has an average grain size of 10.00 nm to 30.00 nm, preferably 12.00 nm to 30.00 nm, preferably 13.60 nm to 25.40 nm, and more preferably 15.20 nm to 25.40 nm.

[0013] The present invention provides a microcrystalline glass with a moth-eye structure, wherein the etching solution comprises the following components in mass percentage: 0.01% to 16.00% of an acid solution, 0% to 18.00% of an additive, and the remainder is water; preferably, the acid solution comprises hydrofluoric acid, and more preferably, the concentration of the hydrofluoric acid is greater than or equal to 40.00wt%; preferably, the additive comprises one or more of barium sulfate, silica sand, and cellulose; more preferably, the particle size of the barium sulfate is less than 2mm and the purity is greater than 98%; more preferably, the particle size of the silica sand is 0.01 to 2.5mm, and the purity is>99.9%; more preferably, the molecular weight of the cellulose is 50000 to 150000, and the crystalline phase accounts for>60wt%; further preferably, the additive comprises 0 to 6.00% of barium sulfate, 0 to 6.00% of silica sand, and 0 to 6.00% of cellulose.

[0014] In the glass-ceramics with a moth-eye-like structure provided by the present invention, the bottom surface of the nanoscale protrusion structure is elliptical, has a major axis A and a minor axis B, the height of the nanoscale protrusion structure in the vertical direction is h, and the nanoscale protrusion structure satisfies the following relationship in the spatial coordinate system (x1, y1, z1):

[0015]

[0016] Formula (1) takes the center point of the major axis A and the minor axis B as the origin, A = B or A ≠ B; x1 is the variable along the major axis A, y1 is the variable along the minor axis B, z1 is the variable along the height h, and 0<|x1|<A / 2, 0<|y1|<B / 2, 0<z1.

[0017] The microcrystalline glass with a moth-eye-like structure provided by the present invention has a long axis A of the bottom surface of the nanoscale protrusion structure in the range of 12.0nm to 65.0nm, preferably 15.00nm to 63.00nm, preferably 16.00nm to 60.00nm; the short axis B of the bottom surface of the nanoscale protrusion structure in the range of 10.0nm to 63.0nm, preferably 11.00nm to 61.0nm, preferably 13.00nm to 60.00nm, more preferably 14.70nm to 60.00nm; the height h of the nanoscale protrusion structure in the vertical direction in the range of 4.50nm to 76.00nm, preferably 4.85nm to 75.40nm, preferably 5.00nm to 70.00nm, more preferably 6.00nm to 70.00nm.

[0018] In the glass-ceramics with a moth-eye-like structure provided by the present invention, in the moth-eye-like structure layer, the spacing L between the bottom surfaces of two adjacent nanoscale protrusion structures ranges from 0nm to 155.00nm; preferably from 0nm to 131.00nm, and more preferably from 0nm to 114.00nm.

[0019] The microcrystalline glass with a moth-eye-like structure provided by the present invention is measured on the surface of the moth-eye-like structure layer on the main surface. When the thickness of the microcrystalline glass with a moth-eye-like structure is 0.64 mm, the transmittance under the wavelength of 550.00 nm light is greater than or equal to 91.00%, preferably greater than or equal to 93.00%, preferably greater than or equal to 95.00%, preferably greater than or equal to 95.50%, preferably greater than or equal to 96.00%; more preferably 91.00% to 99.00%, more preferably 95.00% to 99.00%.

[0020] The glass-ceramics with a moth-eye structure provided by the present invention comprises the following components, calculated based on the mass percentage of oxides:

[0021] SiO2: 70.00%-80.00%;

[0022] Al2O3: 5.00%-10.00%;

[0023] Li2O: 5.00%-15.00%;

[0024] ZrO2: 0%-5.00%;

[0025] P2O5: 0%-5.00%;

[0026] B2O3: 0%-5.00%;

[0027] Na2O: 0%-5.00%.

[0028] In a second aspect, the present invention provides a method for preparing a microcrystalline glass having a moth-eye structure as described above, characterized in that it comprises the following steps: using an etching solution to perform surface etching treatment on the main surface of the microcrystalline glass substrate to obtain a microcrystalline glass having a moth-eye structure.

[0029] In the preparation method provided by the present invention, the etching solution comprises the following components calculated by mass percentage: 0.01% to 16.00% of an acid solution, 0% to 18.00% of an additive, and the remainder is water; preferably, the acid solution comprises hydrofluoric acid, and more preferably, the concentration of the hydrofluoric acid is greater than or equal to 40.00wt%; preferably, the additive comprises one or more of barium sulfate, silica sand, and cellulose; more preferably, the particle size of the barium sulfate is less than 2mm and the purity is greater than 98%; more preferably, the particle size of the silica sand is 0.01 to 2.5mm, and the purity is>99.9%; more preferably, the molecular weight of the cellulose is 50000 to 150000, and the crystalline phase accounts for>60wt%; further preferably, the additive comprises 0 to 6.00% of barium sulfate, 0 to 6.00% of silica sand, and 0 to 6.00% of cellulose.

[0030] In the preparation method provided by the present invention, the surface etching treatment is: placing a microcrystalline glass substrate in an etching solution, performing an ultrasonic etching reaction, and after the reaction is completed, taking out the microcrystalline glass substrate and performing a cleaning treatment and a drying treatment in sequence to obtain a microcrystalline glass with a moth-eye structure; preferably, the temperature of the etching solution is 10 to 80°C; preferably, the time of the ultrasonic etching reaction is 10 to 180 minutes.

[0031] In the preparation method provided by the present invention, the main crystalline phase of the microcrystalline glass substrate includes petalite and lithium silicate; preferably, the main crystalline phase includes petalite, lithium monosilicate and lithium disilicate; or includes petalite and lithium disilicate.

[0032] In the preparation method provided by the present invention, the crystallinity of the microcrystalline glass substrate is greater than or equal to 30.00wt%, preferably greater than or equal to 35.00wt%, further preferably greater than or equal to 40.00wt%, preferably 35.00wt% to 95.00wt%, preferably 40.00wt% to 95.00wt%, preferably 50.00wt% to 95.00wt%, and more preferably 60.00 to 95.00wt%.

[0033] In the preparation method provided by the present invention, the average grain size of the microcrystalline glass substrate is 10.00 nm to 30.00 nm, preferably 12.00 nm to 30.00 nm, preferably 13.60 nm to 25.40 nm, and more preferably 15.20 nm to 25.40 nm.

[0034] In the preparation method provided by the present invention, the bottom surface of the nanoscale protrusion structure is elliptical, has a major axis A and a minor axis B, the height of the nanoscale protrusion structure in the vertical direction is h, and the nanoscale protrusion structure satisfies the following relationship in the spatial coordinate system (x1, y1, z1):

[0035]

[0036] Formula (1) takes the center point of the major axis A and the minor axis B as the origin, A = B or A ≠ B; x1 is the variable along the major axis A, y1 is the variable along the minor axis B, z1 is the variable along the height h, and 0<|x1|<A / 2, 0<|y1|<B / 2, 0<z1.

[0037] In the preparation method provided by the present invention, the range of the major axis A of the bottom surface of the nanoscale protrusion structure is 12.0nm to 65.0nm, preferably 15.00nm to 63.00nm, preferably 16.00nm to 60.00nm; the range of the minor axis B of the bottom surface of the nanoscale protrusion structure is 10.0nm to 63.0nm, preferably 11.00nm to 61.0nm, preferably 13.00nm to 60.00nm, more preferably 14.70nm to 60.00nm; the range of the height h of the nanoscale protrusion structure in the vertical direction is 4.50nm to 76.00nm, preferably 4.85nm to 75.40nm, preferably 5.00nm to 70.00nm, and more preferably 6.00nm to 70.00nm.

[0038] In the preparation method provided by the present invention, in the moth-eye structure layer, the distance L between the bottom surfaces of two adjacent nanoscale protrusion structures ranges from 0 nm to 155.00 nm; preferably from 0 nm to 131.00 nm, and more preferably from 0 nm to 114.00 nm.

[0039] In the preparation method provided by the present invention, the microcrystalline glass substrate includes the following components calculated based on the mass percentage of oxides:

[0040] SiO2: 70.00%-80.00%;

[0041] Al2O3: 5.00%-10.00%;

[0042] Li2O: 5.00%-15.00%;

[0043] ZrO2: 0%-5.00%;

[0044] P2O5: 0%-5.00%;

[0045] B2O3: 0%-5.00%;

[0046] Na2O: 0%-5.00%.

[0047] In the preparation method provided by the present invention, it is measured on the surface of the moth-eye structure layer on the main surface that the transmittance of the microcrystalline glass with a moth-eye structure at a wavelength of 550.00nm is greater than or equal to 91.00% when the thickness is 0.64mm, preferably greater than or equal to 93.00%, preferably greater than or equal to 95.00%, preferably greater than or equal to 95.50%, preferably greater than or equal to 96.00%; more preferably 91.00% to 99.00%, more preferably 95.00% to 99.00%.

[0048] In a third aspect, the present invention provides the use of the above-mentioned microcrystalline glass with a moth-eye structure or the microcrystalline glass with a moth-eye structure prepared by the above-mentioned preparation method in electronic products. Preferably, the electronic product is one or more of a display glass cover, a solar photovoltaic glass substrate, and an LED light-emitting device glass substrate.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] 1. The present invention unexpectedly discovered that by using an etching solution to perform surface etching treatment on a microcrystalline glass substrate of a specific crystal phase system, a moth-eye-like layer with a specific structure can be obtained on the surface of the microcrystalline glass, thereby obtaining a microcrystalline glass with a moth-eye-like structure, and the microcrystalline glass with a moth-eye-like structure has high transmittance in the visible light range.

[0051] 2. The present invention finds that the obtained moth-eye-like structure, i.e., the nanoscale protrusion structure, satisfies a specific relationship in the spatial coordinate system (x1, y1, z1).

[0052] 3. By adjusting the crystallinity, average grain size and other structures of the microcrystalline glass substrate or by adjusting the major axis A and minor axis B, height h and spacing L between the bottom surfaces of adjacent nanoscale protrusions in the moth-eye-like structure, the transmittance of the microcrystalline glass with a moth-eye-like structure obtained after etching can be improved in the visible light range.

[0053] 4. The present invention provides a method for large-scale production of microcrystalline glass with a moth-eye structure with simple process and low cost. This preparation method enables the moth-eye structure itself to form an integral whole with the microcrystalline glass substrate, which can effectively prevent the moth-eye structure from falling off. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a schematic diagram of the microcrystalline glass with a moth-eye structure and its anti-reflection principle described in the present invention.

[0055] Figure 2 Schematic diagram of the spacing L and height h of the moth-eye-like structure of the present invention.

[0056] Figure 3 This is an AFM image of the moth-eye structure of the microcrystalline glass substrate of Example 18 after etching.

[0057] Figure 4 This is the XRD spectrum of the microcrystalline glass substrate in Example 9 whose main crystalline phases are petalite, lithium monosilicate and lithium disilicate.

[0058] Figure 5 This is the XRD spectrum of the microcrystalline glass substrate in Example 19 whose main crystalline phases are petalite and lithium disilicate.

[0059] Figure 6 This is a surface SEM image of the microcrystalline glass substrate of Example 18 after etching.

[0060] Figure 7 This is a surface SEM image of the ordinary glass substrate of Comparative Example 1 after etching.

[0061] Figure 8 This is a surface SEM image of the microcrystalline glass substrate of comparative example 2 whose main crystal phases are zinc magnesium spinel and zirconium oxide after etching.

[0062] Fig. 9 This is a distribution diagram of the A value and B value of Example 18. DETAILED DESCRIPTION

[0063] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.

[0064] Unless otherwise specified in specific circumstances, the numerical ranges listed herein include upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values ​​listed when defining the range. "And / or" herein is inclusive, for example, "A; and / or B" means only A, or only B, or both A and B.

[0065] The relevant special names and relevant measuring methods involved in the present invention are explained as follows.

[0066] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that contains both glass phase and crystal phase and is prepared by targeted controlled crystallization of substrate glass. Note: The crystal phase here may also be called crystal phase, microcrystalline phase, or crystal phase in other patent documents.

[0067] In the present invention, the microcrystalline glass substrate refers to microcrystalline glass that has not been subjected to surface etching treatment.

[0068] Crystalline phase: The crystallographic phase is the microscopic structure of the crystal, which is determined by the conformation and arrangement of the polymer chains in the crystal.

[0069] Crystallinity: the percentage of the total mass of crystals / crystalline phases / grains in the total mass of microcrystalline glass. It should be understood that both crystalline phases and grains refer to crystals precipitated in microcrystalline glass.

[0070] Transmittance: The ratio of the radiant energy that is projected and passes through an object to the total radiant energy that is projected onto the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side.

[0071] The term "disposing" used in the present invention includes a specific structure formed by etching the microcrystalline glass substrate using any etching method known in the art.

[0072] Moth-eye-like structure: also known as bionic moth-eye structure, refers to a structure similar to the compound eye of a moth.

[0073] The moth-eye-like structure in the present invention is an irregularly arranged nano-scale protrusion structure with specific characteristics formed on the surface of the microcrystalline glass substrate after the surface of the microcrystalline glass substrate is etched with an etching solution, and is shaped like a rugby ball.

[0074] The etching reaction mechanism of the present invention is that the glass phase in the microcrystalline glass substrate reacts with HF, and this reaction includes the reaction between HF and SiO2, and the reaction between HF and the metal oxide in the glass phase. For example, the following reaction occurs:

[0075] SiO2+4HF=SiF4↑+2H2O;

[0076] Al2O3+6HF=2AlF3+3H2O;

[0077] Na2O+2HF=2NaF+H2O;

[0078] The reaction product SiF4 is in gaseous state under normal conditions. Part of it will evaporate, and the other part will dissolve in the solution and continue to react, such as the following reactions:

[0079] 4SiF4+2HF+3H2O=3H2SiF6+H2SiO3;

[0080] 3SiF4+2AlF3=Al2(SiF6)3;

[0081] SiF4+2NaF=Na2SiF6.

[0082] Ultimately, the glass phase on the surface of the microcrystalline glass substrate of the present invention is corroded and consumed, leaving acid-resistant crystalline substances such as petalite, lithium monosilicate and lithium disilicate, forming a nanoscale protrusion structure with a specific distribution and a specific morphology on the surface of the microcrystalline glass substrate, that is, forming a moth-eye structure layer with a specific structure.

[0083] In some embodiments, the glass-ceramics with a moth-eye structure of the present invention comprises a glass-ceramics substrate and a moth-eye structure layer disposed on the main surface of the glass-ceramics substrate; and the moth-eye structure layer and the glass-ceramics substrate are integral; the moth-eye structure layer is obtained by etching the main surface of the glass-ceramics substrate using an etching solution. Figure 1As shown, the microcrystalline glass substrate 10 includes opposite main surfaces 11 and 12 ; the moth-eye-like structure layer 13 is disposed on the main surface 11 of the microcrystalline glass substrate.

[0084] In some embodiments, the etching solution of the present invention comprises the following components calculated by mass percentage: 0.01% to 16.00% of an acid solution, 0% to 18.00% of an additive, and the remainder is water.

[0085] Furthermore, the acid solution includes hydrofluoric acid, and preferably the concentration of the hydrofluoric acid is greater than or equal to 40.00 wt %.

[0086] Furthermore, the additive includes one or more of barium sulfate, silica sand, and cellulose; preferably, the particle size of the barium sulfate is less than 2 mm and the purity is greater than 98%; preferably, the particle size of the silica sand is 0.01-2.5 mm and the purity is >99.9%; preferably, the molecular weight of the cellulose is 50,000-150,000, and the crystalline phase accounts for >60wt%; more preferably, the additive includes 0-6.00% of barium sulfate, 0-6.00% of silica sand and 0-6.00% of cellulose.

[0087] Furthermore, preferably, the additive includes 0-6.00% barium sulfate, 0-6.00% silica sand and 0-6.00% cellulose.

[0088] The present invention finds that there is a certain relationship between the structure and crystal phase system of the microcrystalline glass substrate and the optical properties of the microcrystalline glass with a moth-eye structure obtained after etching, and this relationship is linked through the moth-eye structure. The present invention finds that after the microcrystalline glass substrate containing a specific crystal phase system is etched by an etching solution, an irregularly arranged, rugby-shaped nano-scale protrusion structure is formed on the surface of the microcrystalline glass substrate. This structure is exactly the moth-eye structure, such as Figure 3 These randomly and irregularly arranged nano-scale protrusions can form a gradient refractive index between glass and air, effectively increasing the transmittance of microcrystalline glass to visible light, as shown in Figure 2. Figure 1 As shown, the refractive index gradient changes, that is, gradually changes from 1 to 1.5, achieving a high transmittance effect of visible light on the microcrystalline glass with a moth-eye structure.

[0089] In some embodiments, the main crystalline phase of the microcrystalline glass substrate includes petalite, lithium monosilicate and lithium disilicate; or includes petalite and lithium disilicate.

[0090] After further in-depth research, the present invention discovered that a microcrystalline glass substrate with a specific main crystalline phase contains different degrees of crystallinity, which can bring different improvement effects on the transmittance of the microcrystalline glass with a moth-eye structure obtained after etching in the visible light range; among them, a lower degree of crystallinity often leads to less improvement in the transmittance of the microcrystalline glass with a moth-eye structure, because a lower degree of crystallinity indicates that the content of the main crystalline phase in the microcrystalline glass substrate is low, and the nano-scale protrusion structures formed on the microcrystalline glass substrate after etching are not evenly distributed and are small in number, which in turn leads to less improvement in the transmittance of the microcrystalline glass with a moth-eye structure in the visible light range.

[0091] In some embodiments, the crystallinity of the microcrystalline glass substrate of the present invention is preferably greater than or equal to 30.00wt%, preferably greater than or equal to 35.00wt%, preferably greater than or equal to 40.00wt%, further preferably greater than or equal to 50.00wt%, preferably 35.00wt% to 95.00wt%, preferably 40.00wt% to 95.00wt%, preferably 50.00wt% to 95.00wt%, more preferably 60.00 to 95.00wt%, preferably 50.00wt% to 86.00wt%, more preferably 60.00wt% to 86.00wt%; it can also be 60.00wt% to 70.00wt%, 60.00wt% to 80 %. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0092] In addition, the present invention has discovered that the average grain size distribution of a microcrystalline glass substrate having a specific main crystalline phase also exhibits a similar pattern. If the average grain size is too small, the nanoscale protrusion structure formed will be smaller in size. These smaller nanoscale protrusion structures will be distributed very sparsely, weakening the gradient change of the refractive index, resulting in less improvement in the transmittance of the microcrystalline glass with a moth-eye structure in the visible light range.

[0093] In some embodiments, the average grain size of the microcrystalline glass substrate of the present invention is 10.00nm to 30.00nm, preferably 12.00nm to 30.00nm, and more preferably 15.00nm to 30.00nm; it can also be 10.00nm to 20.00nm, 13.00nm to 30.00nm, 20.00nm to 30.00nm, 18.00nm to 27.00nm, 16.00nm to 28.00nm, 19.00nm to 26.00nm, 12.20nm, 13.60nm, 14.80nm 0nm, 25.00nm, 25.40nm, 27.00nm, 30.00nm, etc., and all ranges and subranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0094] The present invention also studies the obtained nanoscale protrusion structure of the microcrystalline glass with a moth-eye structure. The bottom surface of the nanoscale protrusion structure of the present invention is elliptical, has a major axis A and a minor axis B, and the height of the nanoscale protrusion structure in the vertical direction is h. The nanoscale protrusion structure satisfies the following relationship in the spatial coordinate system (x1, y1, z1):

[0095]

[0096] Formula (1) takes the center point of the major axis A and the minor axis B as the origin, A = B or A ≠ B; x1 is the variable along the major axis A, y1 is the variable along the minor axis B, z1 is the variable along the height h, and 0<|x1|<A / 2, 0<|y1|<B / 2, 0<z1.

[0097] In the present invention, the process of obtaining formula (1) is as follows:

[0098] 1. An atomic force microscope (AFM) is used to randomly select a test surface on the etched surface of a glass-ceramic sample having a moth-eye structure; and original surface morphology data of the glass-ceramic sample having a moth-eye structure of the present invention is obtained.

[0099] 2. Import the obtained raw data into the Gwyddion software, select cross-section analysis, and obtain the long axis A of the bottom surface of the nano-scale protrusion structure, the short axis B of the bottom surface of the nano-scale protrusion structure, and the height h of the nano-scale protrusion structure in the vertical direction through analysis. It should be understood that: by analyzing the bottom surface of the nano-scale protrusion structure, the long axis A and the short axis B can be obtained; by analyzing two cross sections perpendicular to the bottom surface of the nano-scale protrusion structure along the long axis A and the short axis B, the height h of the nano-scale protrusion structure in the vertical direction can be obtained.

[0100] 3. Import the original data obtained into the origin software again to construct a 3D morphology map with a large number of nanoscale protrusion structures. This morphology map is exactly the same as the morphology map in the Gwyddion software.

[0101] 4. The 3D topography image obtained in the origin software is processed to obtain the projection on the z=0 plane, and the bottom surface graphics of multiple nanoscale protrusion structures are obtained. The bottom surface graphics of these nanoscale protrusion structures are elliptical. Through fitting, it is found that the bottom surface of the nanoscale protrusion structure satisfies the relationship in the horizontal plane coordinate system (x, y):

[0102]

[0103] In the above relationship, the center point of the major axis A and the minor axis B is the origin, A=B or A≠B; x is the variable along the direction of the major axis A, y is the variable along the direction of the minor axis B, and 0<|x|<A / 2, 0<|y|<B / 2.

[0104] 5. Then, using the above horizontal plane coordinate system as the basis, curve fitting is performed on the nanoscale protrusion structure in the obtained 3D morphology image in the spatial coordinate system. It is found that the nanoscale protrusion structure satisfies the following relationship in the spatial coordinate system (x1, y1, z1):

[0105]

[0106] Formula (1) takes the center point of the major axis A and the minor axis B as the origin, A = B or A ≠ B; x1 is the variable along the major axis A, y1 is the variable along the minor axis B, z1 is the variable along the height h, and 0<|x1|<A / 2, 0<|y1|<B / 2, 0<z1.

[0107] In the present invention, the raw data obtained by the atomic force microscope is imported into the Gwyddion software, and the cross-sectional analysis is selected. By analyzing the bottom surfaces of adjacent nanoscale protrusion structures, the spacing L between the bottom surfaces of adjacent nanoscale protrusion structures can also be obtained; it should be understood that the spacing L between the bottom surfaces of adjacent nanoscale protrusion structures specifically refers to the distance between the intersections of the center connecting line of the bottom surfaces of two adjacent nanoscale protrusion structures and the edge lines of the bottom surfaces of the two nanoscale protrusion structures that are close to each other; specifically, Figure 2 shown.

[0108] When visible light passes through the above-mentioned nanoscale protrusion structures, most of the light will pass through these nanoscale protrusion structures, but a small amount of light will be reflected on the sides of these nanoscale protrusion structures. Its reflected light will serve as new incident light and irradiate the sides of adjacent nanoscale protrusion structures, repeating the previous reflection and transmission process, thereby increasing the overall light transmission. Therefore, the transmittance of the microcrystalline glass having a nanoscale protrusion structure that satisfies the relationship in equation (1) will increase.

[0109] In some embodiments, the range of the major axis A of the bottom surface of the nanoscale protrusion structure is 12.0nm to 65.0nm, and can also be 12.00nm to 60.00nm, 12.00nm to 55.00nm, 12.00nm to 50.00nm, 14.00nm to 55.00nm, 17.00nm to 55.00nm, 20.00nm to 55.00nm, 20.00nm to 60.00nm, 25.00nm to 55.00nm, 25.00nm to 60.00nm, 12.80nm, 14.00nm, 14.80nm, 15.00nm, 15.60nm, 15.90nm, 16.00nm, 16.70nm, 17.20nm, 18.50nm, 19. 00nm, 41.40nm, 42.60nm, 43.60nm, 47.00nm, 50.00nm, 55.00nm, 59.00nm, 60.00nm, 61.70nm, 62.50nm, 63.00nm, 64.00nm, 65.00nm, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0110] In some embodiments, the range of the short axis B of the bottom surface of the nanoscale protrusion structure is 10.0nm to 63.0nm, and can also be 10.00nm to 60.00nm, 13.00nm to 50.00nm, 13.00nm to 55.00nm, 15.00nm to 55.00nm, 17.00nm to 55.00nm, 20.00nm to 60.00nm, 20.00nm to 55.00nm, 25.00nm to 60.00nm, 25.00nm to 55.00nm, 16.00nm to 55.00nm, 11.00nm, 11.80nm, 12.00nm, 13.00nm, 13.90nm, 14.70nm, 15.30nm, 15.70nm, 16.00nm, 16.80nm, 17.50nm , 18.00nm, 19.00nm, 20.40nm, 21.80nm, 22.20nm, 23.40nm, 23.90nm, 24.00nm, 24.80nm , 25.50nm, 27.40nm, 27.0nm, 28.00nm, 29.00nm, 30.00nm, 31.20nm, 32.00nm, 33.00nm, 3 4.10nm, 35.00nm, 37.40nm, 38.00nm, 40.50nm, 43.40nm, 44.20nm, 47.00nm, 50.00nm, 55.00nm, 59.00nm, 60.00nm, 60.70nm, 61.00nm, 62.00nm, 63.00nm, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0111] In some embodiments, the height h of the nanoscale protrusion structure in the vertical direction ranges from 4.50 nm to 76.00 nm, and can also be 5.00 nm to 76.00 nm, 5.00 nm to 70.00 nm, 5.00 nm to 60.00 nm, 6.00 nm to 70.00 nm, 7.00 nm to 68.00 nm, 7.00 nm to 65.00 nm, 7.50 nm to 55.00 nm, 4.85 nm, 5.01 nm, 5.24 nm, 5.45 nm, 6.23 nm, 6.74 nm, 7.02 nm, 8.41 nm, 9.00 nm, 10.00 nm, 15.00 nm, 17.00 nm, 18.00 nm, 19.00 nm, 20.00 nm, 21.00 nm, 22.00 nm, 23.00 nm, 24.00 nm, 25.00 nm, 26.00 nm, 27.00 nm, 28.00 nm, 29.00 nm, 30.00 nm, 31.00 nm, 32.00 nm, 33.00 nm, 34.00 nm, 36.00 nm, 37.00 nm, 38.00 nm, 39.00 nm, 41.00 nm, 42.00 nm, 43.00 nm, 44.00 nm, 45.00 nm, 46.00 nm, 47.00 nm, 48.00 nm, 49.00 nm, 51.00 nm, 52.00 nm, 53.00 nm, 54.00 nm, 55.00 .00nm, 20.00nm, 25.00nm, 30.00nm, 35.00nm, 37.41nm, 38.65nm, 40.00nm, 43.66nm, 45.00nm, 47.60nm, 48.00nm, 49.00nm, 50.00nm, 51.20nm, 54.10nm, 56.70nm, 58.70nm, 61.40nm, 62.10nm, 65.00nm, 67.70nm, 69.80nm, 70.00nm, 73.20nm, 75.40nm, 76.00nm, etc., and all ranges and subranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0112] In some embodiments, in the moth-eye structure layer, the spacing L between the bottom surfaces of two adjacent nanoscale protrusion structures ranges from 0nm to 155.00nm; preferably 0nm to 150.00nm, and can also be 0nm to 130.00nm, 0nm to 124.00nm, 0nm to 114.00nm, 0nm to 104.00nm, 0nm to 95.00nm, 0nm to 80.00nm, 0nm to 76.50nm, 0nm to 74.40nm, 0nm to 73.20nm, 0nm to 71.10nm, 0nm to 67.40nm, 0nm to 62.50nm, 0nm to 54.40nm, 0nm to 40.00nm, 0nm to 35.40nm, 0nm to 33.50nm, 0nm to 31.90nm, 0nm to 30.10nm, 0nm to 30.00nm, etc.

[0113] In some embodiments, the present invention is measured on the surface of the moth-eye structure layer on the main surface, and the transmittance of the microcrystalline glass with a moth-eye structure at a wavelength of 550.00nm is greater than or equal to 91.00%, preferably greater than or equal to 93.00%, preferably greater than or equal to 95.00%, more preferably greater than or equal to 96.00%, and can also be 95.00% to 96.00%, 96.00% to 97.00%, 98.00% to 99.00%, 91 ... %, 97.00% to 98.00%, 95.50% to 96.50%, 95.50% to 99.50%, 91.00%, 92.00%, 93.00%, 94.00%, 95.0%, 95.50%, 96.00%, 96.50%, 97.00%, 97.50%, 98.00%, 98.50%, 99.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0114] In some embodiments, the microcrystalline glass substrate of the present invention includes the following components calculated based on the mass percentage of oxides:

[0115] SiO2: 70.00%-80.00%;

[0116] Al2O3: 5.00%-10.00%;

[0117] Li2O: 5.00%-15.00%;

[0118] ZrO2: 0%-5.00%;

[0119] P2O5: 0%-5.00%;

[0120] B2O3: 0%-5.00%;

[0121] Na2O: 0%-5.00%.

[0122] SiO2 is a glass network former oxide and an indispensable component for forming a glass network structure. In the present invention, the content of SiO2 is 70.00%-80.00%, 71.00%-73.00%, 71.00%-75.00%, 73.00%-75.50%, 72.50%-78.60%, 71.50%-76.90%, 74.50%-78.60%, 71.00%, 72.00%, 73.00%, 74.00%, 75.00%, 76.00%, 77.00%, 78.00%, 79.00%, 80.00%, etc., and all ranges and sub-ranges between the above values.

[0123] Al2O3 is an intermediate oxide in glass formation, which can improve the chemical stability of glass. In the present invention, the content of Al2O3 is 5.00% to 10.00%, 5.00% to 6.00%, 5.00% to 7.00%, 5.00% to 8.00%, 5.00% to 9.00%, 6.00% to 7.00%, 6.00% to 8.00%, 7.00% to 9.00%, 7.00% to 10.00%, 8.00% to 9.00%, 8.00% to 10.00%, 9.00% to 10.00%, 5.00%, 6.00%, 7.00%, 8.00%, 9.00%, 10.00%, etc., and all ranges and sub-ranges between the above values.

[0124] The content of Li2O is 5.00% to 15.00%, 5.00% to 8.00%, 5.00% to 10.00%, 5.00% to 11.00%, 5.00% to 14.00%, 6.00% to 9.00%, 6.00% to 12.00%, 7.00% to 14.00%, 8.00% to 11.00%, 9.00% to 15.00%, 8.00% to 13.00%, 6.00% to 11.00%, 5.00%, 6.00%, 8.00%, 9.00%, 10.00%, 11.00%, 12.00%, 13.00%, 14.00%, 15.00%, etc., and all ranges and sub-ranges between the above values.

[0125] ZrO2 has a large accumulation effect on the glass structure due to its high cationic charge and strong field, and is used as a nucleating agent in the glass substrate; at the same time, ZrO2 can also increase the strength and toughness of microcrystalline glass and improve its acid and alkali corrosion resistance. In the present invention, the content of ZrO2 is 0%-5.00%, 0%-1.00%, 0%-2.00%, 1.00%-4.00%, 1.00%-3.00%, 1.50%-4.50%, 2.80%-3.70%, 1.90%-3.50%, 1.40%-4.90%, 0%, 1.00%, 2.00%, 3.00%, 4.00%, 5.00%, etc., as well as all ranges and sub-ranges between the above values.

[0126] P2O5 is a glass-forming oxide, which exists in the network structure as phosphorus-oxygen tetrahedron [PO4]; P2O5 has a fluxing effect and can effectively inhibit the precipitation of coarse ZrO2 crystals. In the present invention, the content of P2O5 is 0% to 5.00%, 0% to 1.00%, 0% to 2.00%, 1.00% to 4.00%, 1.00% to 3.00%, 1.50% to 4.50%, 2.80% to 3.70%, 1.90% to 3.50%, 1.40% to 4.90%, 0%, 1.00%, 2.00%, 3.00%, 4.00%, 5.00%, etc., and all ranges and sub-ranges between the above values.

[0127] B2O3 helps to reduce the melting temperature of the substrate glass. In the present invention, the content of B2O3 is 0% to 5.00%, 0% to 1.00%, 0% to 2.00%, 1.00% to 4.00%, 1.00% to 3.00%, 1.50% to 4.50%, 2.80% to 3.70%, 1.90% to 3.50%, 1.40% to 4.90%, 0%, 1.00%, 2.00%, 3.00%, 4.00%, 5.00%, etc., and all ranges and sub-ranges between the above values.

[0128] Na2O is an oxide outside the glass network, which can provide free oxygen to increase the oxygen-silicon ratio in the glass structure, break bonds, increase the thermal expansion coefficient of the glass, and play an important role in adjusting the grain size, crystal phase composition, and crystal phase ratio. In the present invention, the content of Na2O is 0% to 5.00%, 0% to 1.00%, 0% to 2.00%, 1.00% to 4.00%, 1.00% to 3.00%, 1.50% to 4.50%, 2.80% to 3.70%, 1.90% to 3.50%, 1.40% to 4.90%, 0%, 1.00%, 2.00%, 3.00%, 4.00%, 5.00%, etc., and all ranges and sub-ranges between the above values.

[0129] In some embodiments, the preparation method of the microcrystalline glass substrate described in the present invention may include but is not limited to the following steps: mixing the raw materials according to the formula, melting and molding, annealing and cooling, and the molding methods include float, overflow, rolling and pouring, etc., to obtain the substrate glass.

[0130] In some embodiments, the microcrystalline glass substrate of the present invention is obtained by heat treatment of substrate glass, and the heat treatment includes nucleation treatment and / or crystallization treatment. It should be understood that when the substrate glass is heat treated, one-step heat treatment or two-step or multi-step heat treatment can be performed. If a one-step heat treatment is performed, it means that the nucleation treatment is not performed separately, and the nucleation and target crystal growth are directly performed in a one-step heating process, which can be understood as directly performing a crystallization treatment. If a two-step heat treatment is performed, it means that a two-step heating process is performed, first a nucleation treatment, i.e., a nucleation treatment, is performed, and then a target crystal growth treatment, i.e., a crystallization treatment, is performed. In some embodiments, the heat treatment may include (i) heating the pre-nucleated crystallizable glass to a nucleation temperature (T0) at a rate of 1-10°C / min; (ii) maintaining the crystallizable glass at the nucleation temperature for a time period of about 60 min to 300 min, thereby forming a nucleated crystallizable glass; (iii) heating the nucleated crystallizable glass to a crystallization temperature (T1) at a rate of 1-10°C / min; (iv) maintaining the nucleated crystallizable glass at the crystallization temperature for a time period of about 5 min to 240 min.

[0131] In some embodiments, the main crystalline phase of the microcrystalline glass substrate of the present invention includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the crystallinity of the microcrystalline glass substrate is 35.00wt% to 95.00wt%, preferably 35.00wt% to 90.00wt%, preferably 40.00wt% to 90.00wt%, preferably 50.00wt% to 85.00wt%, preferably 60.00wt% to 90wt%, preferably 60.00wt% to 80wt%, more preferably 60.00wt% to 70.00wt%, more preferably 80.00wt% to 85.00wt%. .00wt%;It can also be 60.00wt%~70.00wt%, 63.00wt%~77.00wt%, 65.00wt%~75.00wt%, 68.00wt%~84.00wt%, 69.00wt%~83.00wt%, 35.00wt%, 40.00wt%, 50.00wt%, 60.00wt%, 65.00wt%, 70.00wt%, 75.00wt%, 80.00wt%, 85.00wt%, 90.00wt%, 95.00wt%, etc., and all ranges and sub-ranges between the above values. It should be understood that in an embodiment, any of the above ranges can be combined with any other ranges.

[0132] In some embodiments, the main crystalline phase of the microcrystalline glass substrate of the present invention includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the average grain size of the microcrystalline glass substrate is 10.00nm~30.00nm, preferably 12.00nm~30.00nm, preferably 13.60nm~25.40nm, preferably 15.20nm~25.40nm, and can also be 10.00nm~20.00nm, 13.00nm~30.00nm, 15.00nm~30.00nm, 25.00nm~30.00nm, 18.00nm~27.00nm, 16.00nm~28.00nm , 19.00nm to 26.00nm, 12.00nm, 13.60nm, 14.80nm, 15.00nm, 15.20nm, 15.60nm, 15.80nm, 16.70nm, 16.90nm, 17.20nm, 17.40nm, 18.00nm, 18.50nm, 18.60nm, 19.50nm, 20.00nm, 21.20nm, 22.60nm, 22.80nm, 23.00nm, 23.30nm, 24.20nm, 25.00nm, 25.40nm, 27.00nm, 30.00nm, etc., and all ranges and subranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0133] In some embodiments, the main crystalline phase of the microcrystalline glass substrate of the present invention includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; measured on the surface of the moth-eye structure layer on the main surface, the microcrystalline glass with the moth-eye structure is 0.64 mm thick, and the transmittance under the wavelength of 550.00 nm is greater than or equal to 91.00%, preferably greater than or equal to 93.00%, preferably greater than or equal to 95.00%, more preferably greater than or equal to 96.00%, and can also be 95. %, 95.00% to 95.50%, 96.00% to 96.50%, 97.00% to 98.00%, 98.00% to 99.50%, 91.00%, 92.00%, 93.00%, 94.00%, 95.00%, 95.50%, 96.00%, 96.50%, 97.00%, 97.50%, 98.00%, 98.50%, 99.00%, etc., and all ranges and subranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0134] In some embodiments, the main crystalline phase of the microcrystalline glass substrate of the present invention includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the bottom surface of the nanoscale protrusion structure is elliptical, having a major axis A and a minor axis B, the height of the nanoscale protrusion structure in the vertical direction is h, and the nanoscale protrusion structure satisfies the following relationship in the spatial coordinate system (x1, y1, z1):

[0135]

[0136] Formula (1) takes the center point of the major axis A and the minor axis B as the origin, A = B or A ≠ B; x1 is the variable along the major axis A, y1 is the variable along the minor axis B, z1 is the variable along the height h, and 0<|x1|<A / 2, 0<|y1|<B / 2, 0<z1.

[0137] In some embodiments, the main crystalline phase of the microcrystalline glass substrate of the present invention includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the range of the major axis A of the bottom surface of the nanoscale protrusion structure is 12.0nm to 65.0nm, preferably 15.00nm to 63.00nm, preferably 16.00nm to 60.00nm, more preferably 18.50nm to 60.00nm, preferably 21.40nm to 60.00nm; the nanoscale protrusion The short axis B of the bottom surface of the structure ranges from 10.0nm to 63.0nm, preferably from 11.00nm to 61.0nm, preferably from 13.00nm to 60.00nm, and more preferably from 14.70nm to 60.00nm; the height h of the nanoscale protrusion structure in the vertical direction ranges from 4.50nm to 76.00nm, preferably from 4.85nm to 75.40nm, preferably from 5.00nm to 70.00nm, and more preferably from 6.00nm to 70.00nm.

[0138] In some embodiments, the main crystal phase of the microcrystalline glass substrate of the present invention includes petalite, lithium monosilicate and lithium disilicate, or the main crystal phase includes petalite and lithium disilicate; in the moth-eye structure layer, the spacing L between the bottom surfaces of two adjacent nanoscale protrusion structures ranges from 0nm to 155.00nm; preferably 0nm to 131.00nm, and more preferably 0nm to 114.00nm.

[0139] In some embodiments, the main crystalline phase of the microcrystalline glass substrate of the present invention includes petalite, lithium monosilicate and lithium disilicate; the crystallinity of the microcrystalline glass substrate is 60.00wt%~85.00wt%, preferably 60.00wt%~80.00wt%, preferably 60.00wt%~70.00wt%; the average grain size of the microcrystalline glass substrate is 15.0nm~25.40nm, preferably 15.20nm~25.40nm, preferably 15.60nm~25.40nm, preferably 16.70nm~25.40nm; measured on the surface of the moth-eye structure layer on the main surface, the microcrystalline glass with a moth-eye structure is 0.64mm thick and has a transmittance of 95.00%~99.00% under light of 550.00nm wavelength.

[0140] In some embodiments, the main crystalline phase of the microcrystalline glass substrate of the present invention includes petalite and lithium disilicate, and the crystallinity is 60.00wt% to 85.00wt%, preferably 60.00wt% to 80.00wt%, preferably 60.00wt% to 70.00wt%, and the average grain size of the microcrystalline glass substrate is 15.00nm to 25.40nm, preferably 15.20nm to 25.40nm, and more preferably 15.60nm to 25.40nm; it is measured on the surface of the moth-eye structure layer on the main surface that the microcrystalline glass with a moth-eye structure has a transmittance of 95.00% to 99.00% under light of 550.00nm wavelength when the thickness is 0.64mm.

[0141] In some embodiments, the main crystalline phase of the microcrystalline glass substrate of the present invention includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the crystallinity of the microcrystalline glass substrate is 60.00wt% to 85.00wt%, preferably 60.00wt% to 80.00wt%, preferably 60.00wt% to 70.00wt%; the average grain size of the microcrystalline glass substrate is 15.0nm to 25.40nm, preferably 15.20nm to 25.40nm, preferably 15.60nm to 25.40nm, preferably 16.7 0nm~25.40nm; the major axis A of the bottom surface of the nanoscale protrusion structure ranges from 14.80nm~63.00nm, preferably 17.50nm~62.50nm; the minor axis B of the bottom surface of the nanoscale protrusion structure ranges from 13.90nm~61.00nm, preferably 15.00~59.00nm; the height h of the nanoscale protrusion structure in the vertical direction ranges from 6.00nm~75.00nm; in the moth-eye structure layer, the spacing L between the bottom surfaces of two adjacent nanoscale protrusion structures is 0nm~76.50nm, preferably 0nm~75.00nm.

[0142] In some embodiments, the main crystalline phase of the microcrystalline glass substrate of the present invention includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the range of the major axis A of the bottom surface of the nanoscale protrusion structure is 14.80nm~63.00nm, preferably 17.50nm~62.50nm; the range of the minor axis B of the bottom surface of the nanoscale protrusion structure is 13.90nm~61.00nm, preferably 15.00~59.00nm; the nanoscale The height h of the protruding structure in the vertical direction ranges from 6.00nm to 75.00nm; in the moth-eye structure layer, the spacing L between the bottom surfaces of two adjacent nanoscale protruding structures ranges from 0nm to 76.50nm, preferably from 0nm to 75.00nm; it is measured on the surface of the moth-eye structure layer on the main surface that the microcrystalline glass with a moth-eye structure has a transmittance of 95.00% to 99.00% under light at 550nm when the thickness is 0.64mm.

[0143] The present invention also provides a method for preparing the microcrystalline glass having a moth-eye structure as described above, which comprises the following steps: using an etching solution to perform surface etching on the main surface of the microcrystalline glass substrate to obtain the microcrystalline glass having a moth-eye structure.

[0144] Further, the etching solution comprises the following components calculated by mass percentage: 0.01% to 16.00% of an acid solution, 0% to 18.00% of an additive, and the remainder is water; preferably, the acid solution comprises hydrofluoric acid, and more preferably, the concentration of the hydrofluoric acid is greater than or equal to 40.00wt%; preferably, the additive comprises one or more of barium sulfate, silica sand, and cellulose; more preferably, the particle size of the barium sulfate is less than 2mm and the purity is greater than 98%; more preferably, the particle size of the silica sand is 0.01 to 2.5mm, and the purity is>99.9%; more preferably, the molecular weight of the cellulose is 50000 to 150000, and the crystalline phase accounts for>60wt%; further preferably, the additive comprises 0 to 6.00% of barium sulfate, 0 to 6.00% of silica sand, and 0 to 6.00% of cellulose.

[0145] Furthermore, the surface etching treatment is: placing the microcrystalline glass substrate in an etching solution, performing an ultrasonic etching reaction, and after the reaction is completed, taking out the microcrystalline glass substrate and performing a cleaning treatment and a drying treatment in sequence to obtain a microcrystalline glass with a moth-eye structure; preferably, the temperature of the etching solution is 10 to 80°C; preferably, the time of the ultrasonic etching reaction is 10 to 180 minutes.

[0146] Further, the crystallinity of the microcrystalline glass substrate is preferably greater than or equal to 30.00wt%, preferably greater than or equal to 35.00wt%, preferably greater than or equal to 40.00wt%, further preferably greater than or equal to 50.00wt%, preferably 35.00wt% to 95.00wt%, preferably 40.00wt% to 95.00wt%, preferably 50.00wt% to 95.00wt%, preferably 60.00 to 95.00wt%, preferably 50.00wt% to 86.00wt%, more preferably 60.00wt% to 86.00wt; it can also be 60.00wt% to 70.00wt%, 60.00wt% to 80.00wt%. %, 68.00wt%~84.00wt%, 63.00wt%~77.00wt%, 70.00wt%~90.00wt%, 75.00wt%~85.00wt%, 80.00wt%~90.00wt%, 10wt%, 12wt%, 20wt%, 30wt%, 35.00wt%, 40.00wt%, 50.00wt%, 60.00wt%, 65.00wt%, 70.00wt%, 75.00wt%, 80.00wt%, 86.00wt%, 90.00wt%, 95.00wt% etc., and all ranges and sub-ranges between the above values. It should be understood that in an embodiment, any of the above ranges can be combined with any other ranges.

[0147] Further, the average grain size of the microcrystalline glass substrate is 10.00nm to 30.00nm, preferably 12.00nm to 30.00nm, and more preferably 15.00nm to 30.00nm; it can also be 10.00nm to 20.00nm, 13.00nm to 30.00nm, 20.00nm to 30.00nm, 18.00nm to 27.00nm, 16.00nm to 28.00nm, 19.00nm to 26.00nm, 12.20nm, 13.60nm, 14.80nm, 15.90nm, 16.10nm, 17.20nm, 18.00nm to 29.00nm, 19.00nm to 20.0 ... 0nm, 25.00nm, 25.40nm, 27.00nm, 30.00nm, etc., and all ranges and subranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0148] Furthermore, the bottom surface of the nanoscale protrusion structure is elliptical, having a major axis A and a minor axis B, the height of the nanoscale protrusion structure in the vertical direction is h, and the nanoscale protrusion structure satisfies the following relationship in the spatial coordinate system (x1, y1, z1):

[0149]

[0150] Formula (1) takes the center point of the major axis A and the minor axis B as the origin, A = B or A ≠ B; x1 is the variable along the major axis A, y1 is the variable along the minor axis B, z1 is the variable along the height h, and 0<|x1|<A / 2, 0<|y1|<B / 2, 0<z1.

[0151] Further, the range of the major axis A of the bottom surface of the nanoscale protrusion structure is 12.0nm to 65.0nm, and can also be 12.00nm to 60.00nm, 12.00nm to 55.00nm, 12.00nm to 50.00nm, 14.00nm to 55.00nm, 17.00nm to 55.00nm, 20.00nm to 55.00nm, 20.00nm to 60.00nm, 25.00nm to 55.00nm, 25.00nm to 60.00nm, 12.80nm, 14.00nm, 14.80nm, 15.00nm, 15.60nm, 15.90nm, 16.00nm, 16.70nm, 17.20nm, 18.50nm, 19.00nm 00nm, 41.40nm, 42.60nm, 43.60nm, 47.00nm, 50.00nm, 55.00nm, 59.00nm, 60.00nm, 61.70nm, 62.50nm, 63.00nm, 64.00nm, 65.00nm, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0152] Furthermore, the range of the short axis B of the bottom surface of the nanoscale protrusion structure is 10.0nm to 63.0nm, and can also be 10.00nm to 60.00nm, 13.00nm to 50.00nm, 13.00nm to 55.00nm, 15.00nm to 55.00nm, 17.00nm to 55.00nm, 20.00nm to 60.00nm, 20.00nm to 63.0nm. ~55.00nm, 25.00nm~60.00nm, 25.00nm~55.00nm, 16.00nm~55.00nm, 11.00nm, 11.80nm , 12.00nm, 13.00nm, 13.90nm, 14.70nm, 15.30nm, 15.70nm, 16.00nm, 16.80nm, 17.50nm, 18.00nm, 19.00nm, 20.40nm, 21.80nm, 22.20nm, 23.40nm, 23.90nm, 24.00nm, 24.80nm, 25.50nm, 27.40nm, 27.0nm, 28.00nm, 29.00nm, 30.00nm, 31.20nm, 32.00nm, 33.00nm, 34 .10nm, 35.00nm, 37.40nm, 38.00nm, 40.50nm, 43.40nm, 44.20nm, 47.00nm, 50.00nm, 55.00nm, 59.00nm, 60.00nm, 60.70nm, 61.00nm, 62.00nm, 63.00nm, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0153] Furthermore, the height h of the nanoscale protrusion structure in the vertical direction ranges from 4.50nm to 76.00nm, and can also be 5.00nm to 76.00nm, 5.00nm to 70.00nm, 5.00nm to 60.00nm, 6.00nm to 70.00nm, 7.00nm to 68.00nm, 7.00nm to 65.00nm, 7.50nm to 55.00nm, 4.85nm, 5.01nm, 5.24nm, 5.45nm, 6.23nm, 6.74nm, 7.02nm, 8.41nm, 9.00nm, 10.00nm, 15.00nm, 17.0 .00nm, 72.00nm, 73.20nm, 74.40nm, 75.40nm, 76.00nm, etc., and all ranges and subranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0154] Further, in the moth-eye structure layer, the spacing L between the bottom surfaces of two adjacent nanoscale protrusion structures ranges from 0nm to 155.00nm; preferably 0nm to 150.00nm, and can also be 0nm to 130.00nm, 0nm to 124.00nm, 0nm to 114.00nm, 0nm to 104.00nm, 0nm to 95.00nm, 0nm to 80.00nm, 0nm to 76.50nm, 0nm to 74.40nm, 0nm to 73.20nm, 0nm to 71.10nm, 0nm to 67.40nm, 0nm to 62.50nm, 0nm to 54.40nm, 0nm to 40.00nm, 0nm to 35.40nm, 0nm to 33.50nm, 0nm to 31.90nm, 0nm to 30.10nm, 0nm to 30.00nm, etc.

[0155] Further, it is measured on the surface of the moth-eye structure layer on the main surface that the transmittance of the microcrystalline glass having a moth-eye structure at a wavelength of 550.00nm is greater than or equal to 91.00%, preferably greater than or equal to 93.00%, preferably greater than or equal to 95.00%, more preferably greater than or equal to 96.00%, and can also be 95.00% to 96.00%, 96.00% to 97.00%, 98.00% to 99.00%, 100% to 100% or more. %, 97.00% to 98.00%, 95.50% to 96.50%, 95.50% to 99.50%, 91.00%, 92.00%, 93.00%, 94.00%, 95.0%, 95.50%, 96.00%, 96.50%, 97.00%, 97.50%, 98.00%, 98.50%, 99.00%, etc., and all ranges and subranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0156] Further, according to the mass percentage of oxides, the microcrystalline glass substrate includes the following components:

[0157] SiO2: 70.00%-80.00%;

[0158] Al2O3: 5.00%-10.00%;

[0159] Li2O: 5.00%-15.00%;

[0160] ZrO2: 0%-5.00%;

[0161] P2O5: 0%-5.00%;

[0162] B2O3: 0%-5.00%;

[0163] Na2O: 0%-5.00%.

[0164] Further, the main crystalline phase of the microcrystalline glass substrate includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the crystallinity of the microcrystalline glass substrate is preferably 35.00wt% to 95.00wt%, preferably 40.00wt% to 95.00wt%, preferably 50.00wt% to 95.00wt%, preferably 60.00 to 95.00wt%, preferably 50.00wt% to 85.00wt%, preferably 60.00wt% to 90wt%, preferably 60.00wt% to 80wt%, more preferably 60.00wt% to 70.00wt%, more preferably 80.00wt% to 90.00wt%. %~85.00wt%;It can also be 60.00wt%~70.00wt%, 63.00wt%~77.00wt%, 65.00wt%~75.00wt%, 68.00wt%~84.00wt%, 69.00wt%~83.00wt%, 35.00wt%, 40.00wt%, 50.00wt%, 60.00wt%, 65.00wt%, 70.00wt%, 75.00wt%, 80.00wt%, 85.00wt%, 90.00wt%, 95.00wt% etc., and all ranges and sub-ranges between the above numerical values. It should be understood that in an embodiment, any of the above ranges can be combined with any other ranges.

[0165] Further, the main crystalline phase of the microcrystalline glass substrate includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the average grain size of the microcrystalline glass substrate is 10.00nm~30.00nm, preferably 12.00nm~30.00nm, preferably 13.60nm~25.40nm, preferably 15.20nm~25.40nm, and can also be 10.00nm~20.00nm, 13.00nm~30.00nm, 15.00nm~30.00nm, 25.00nm~30.00nm, 18.00nm~27.00nm, 16.00nm~28.00nm, 19.00nm~29.00nm, 20.00nm~21.00nm, 21.00nm~23.00nm, 23.00nm~24.00nm, 24.00nm~25.00nm, 25.00nm~26.00nm, 26.00nm~27.00nm, 27.00nm~28.00nm, 28.00nm~29.00nm, 29 ... 0nm, 24.20nm, 25.00nm, 25.40nm, 27.00nm, 30.00nm, etc., and all ranges and subranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0166] Further, the main crystalline phase of the microcrystalline glass substrate includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; measured on the surface of the moth-eye structure layer on the main surface, the microcrystalline glass with a moth-eye structure is greater than or equal to 91.00% at a wavelength of 550.00nm when the thickness is 0.64mm, preferably greater than or equal to 93.00%, preferably greater than or equal to 95.00%, and can also be 95.00% to 96.00%. %, 96.00% to 97.00%, 97.00% to 98.00%, 95.50% to 96.50%, 95.50% to 99.50%, 91.00%, 92.00%, 93.00%, 94.00%, 95.00%, 95.50%, 96.00%, 96.50%, 97.00%, 97.50%, 98.00%, 98.50%, 99.00%, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0167] Further, the main crystalline phase of the microcrystalline glass substrate includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the bottom surface of the nanoscale protrusion structure is elliptical, has a major axis A and a minor axis B, the height of the nanoscale protrusion structure in the vertical direction is h, and the nanoscale protrusion structure satisfies the following relationship in the spatial coordinate system (x1, y1, z1):

[0168]

[0169] Formula (1) takes the center point of the major axis A and the minor axis B as the origin, A = B or A ≠ B; x1 is the variable along the major axis A, y1 is the variable along the minor axis B, z1 is the variable along the height h, and 0<|x1|<A / 2, 0<|y1|<B / 2, 0<z1.

[0170] Further, the main crystalline phase of the microcrystalline glass substrate includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the range of the major axis A of the bottom surface of the nanoscale protrusion structure is 12.0nm to 65.0nm, preferably 15.00nm to 63.00nm, preferably 16.00nm to 60.00nm, more preferably 18.50nm to 60.00nm, preferably 21.40nm to 60.00nm; the nanoscale protrusion structure The short axis B of the bottom surface ranges from 10.0nm to 63.0nm, preferably from 11.00nm to 61.0nm, preferably from 13.00nm to 60.00nm, and more preferably from 14.70nm to 60.00nm; the height h of the nanoscale protrusion structure in the vertical direction ranges from 4.50nm to 76.00nm, preferably from 4.85nm to 75.40nm, preferably from 5.00nm to 70.00nm, and more preferably from 6.00nm to 70.00nm.

[0171] Furthermore, the main crystal phase of the microcrystalline glass substrate includes petalite, lithium monosilicate and lithium disilicate, or the main crystal phase includes petalite and lithium disilicate; in the moth-eye structure layer, the spacing L between the bottom surfaces of two adjacent nanoscale protrusion structures is 0 to 155.00 nm; preferably 0 to 131.00 nm, and more preferably 0 to 114.00 nm.

[0172] Further, the main crystalline phase of the microcrystalline glass substrate includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the crystallinity of the microcrystalline glass substrate is 60.00wt% to 85.00wt%, preferably 60.00wt% to 80.00wt%, preferably 60.00wt% to 70.00wt%; the average grain size of the microcrystalline glass substrate is 15.00nm to 25.40nm, preferably 15.20nm to 25.40nm, preferably 15.60nm to 25.40nm, preferably 16.70nm ~25.40nm; the major axis A of the bottom surface of the nanoscale protrusion structure ranges from 14.80nm to 63.00nm, preferably from 17.50nm to 62.50nm; the minor axis B of the bottom surface of the nanoscale protrusion structure ranges from 13.90nm to 61.00nm, preferably from 15.00nm to 59.00nm; the height h of the nanoscale protrusion structure in the vertical direction ranges from 6.00nm to 75.00nm; in the moth-eye structure layer, the spacing L between the bottom surfaces of two adjacent nanoscale protrusion structures is 0nm to 76.50nm, preferably from 0nm to 75.00nm.

[0173] Further, the main crystalline phase of the microcrystalline glass substrate includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate; the range of the major axis A of the bottom surface of the nanoscale protrusion structure is 14.80nm~63.00nm, preferably 17.50nm~62.50nm; the range of the minor axis B of the bottom surface of the nanoscale protrusion structure is 13.90nm~61.00nm, preferably 15.00nm~59.00nm; the range of the minor axis B of the bottom surface of the nanoscale protrusion structure is 13.90nm~61.00nm, preferably 15.00nm~59.00nm; The height h of the structure in the vertical direction ranges from 6.00nm to 75.00nm; in the moth-eye structure layer, the spacing L between the bottom surfaces of two adjacent nanoscale protrusion structures is 0nm to 76.50nm, preferably 0nm to 75.00nm; it is measured on the surface of the moth-eye structure layer on the main surface that the microcrystalline glass with the moth-eye structure has a transmittance of 95.00% to 99.00% under light at 550nm when the thickness is 0.64mm.

[0174] The application of the above-mentioned microcrystalline glass with a moth-eye structure or the microcrystalline glass with a moth-eye structure prepared by the above-mentioned preparation method in electronic products is preferably one or more of a display glass cover, a solar photovoltaic glass substrate, and a LED light-emitting device glass substrate.

[0175] The various glass products of the present invention were tested using the following methods:

[0176] XRD test: The microcrystalline glass sample is ground into glass fine powder with a grinding machine, and its particle size is less than 75μm, and then it is tested by an X-ray diffractometer (Shimadzu's XRD-6100) to obtain an XRD diffraction peak curve. The X-ray diffractometer used in the present invention is Shimadzu's XRD-6100, the target material is copper, the test incident angle range is 2θ=10-80°, the scanning speed is 0.02-6° / min, the working voltage is 40kV, and the working current is 30mA. The XRD diffraction data is analyzed by JADE software to obtain the crystal phase of the sample.

[0177] Average grain size: Using the result data obtained from the XRD test, according to the Scherrer formula D = Kλ / (βcosθ), we can calculate the average grain size of the sample, where λ is the X-ray wavelength of 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction spectrum) output by the XRD instrument is curve-fitted in the Jade software, and Jade outputs a fitting report. According to the angle 2θ value and Peak FWHM value (half-height width of the diffraction peak) corresponding to each diffraction peak in the fitting report, and the Peak FWHM value is converted into radians β = (FWHM / 180*3.14), the grain size of each diffraction peak is calculated by D = Kλ / (βcosθ) and then averaged to obtain the average grain size.

[0178] Testing method for crystal content / crystallinity: Import the X-ray diffractometer test result file (RAW format) into the X-ray diffraction data Rietveld refinement software (such as Gsas, Fullprof, Maud), perform fitting and calculation, and then obtain the crystal content / crystallinity in the microcrystalline glass sample. The ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content, which is also referred to as crystallinity in the present invention.

[0179] Atomic force microscope (AFM) test: The 50*50*0.64mm glass-ceramic sample was cleaned with alcohol and water, and then the glass surface with the moth-eye structure layer was tested using an atomic force microscope (Dimension EDGE) to obtain the sample surface morphology of the 7 micron*7 micron test surface, with 256*256 sampling points on each surface. The FLT file output by the atomic force microscope was opened in the Gwyddion software, and the size of the sample microscopic morphology could be measured through the cross-section analysis function.

[0180] SEM test: The selected microcrystalline glass slices were ultrasonically cleaned and dried, and gold was sprayed on the surface of the sample after drying. The sample was scanned and photographed using a Zeiss Sigma 300 thermal field emission scanning electron microscope (SEM) to obtain a surface morphology of the microcrystalline glass with clear grain boundaries. The magnifications after shooting were 1.00KX, 10.00KX, and 100.00KX.

[0181] Transmittance test: Test according to GB / T 7962.12-2010 Test method for colorless optical glass Part 12: Spectral transmittance. First, clean the glass-ceramic sample in an ultrasonic cleaner. The cleaning conditions are: cleaning time 5-10min; cleaning agent used: commonly used detergent diluted 10 times; cleaning temperature: 45℃-65℃; cleaning frequency: 20KHZ-40KHZ. Then use a haze meter (Japan Konica Minolta spectrophotometer CM-3600A) to test its transmittance under different wavelengths of light.

[0182] Method for obtaining the transmittance results under light of 550nm wavelength: Use Japan Konica Minolta spectrophotometer CM-3600A to test on the main surface of 5 parallel samples before etching or on the surface of the moth-eye structure layer on the main surface of the parallel samples with moth-eye-like structure after etching, and obtain the transmittance of each parallel sample under light of 550nm wavelength before etching and after etching, and then calculate the average transmittance of the 5 parallel samples under light of 550nm wavelength as the transmittance result of the sample to be tested under light of 550nm wavelength.

[0183] Glass thickness: Determined by micrometer testing.

[0184] The present invention is described by specific embodiments:

[0185] The microcrystalline glass substrates used in Examples 1-20 in the following table of the present invention include the following components calculated by the mass percentage of oxides: SiO2: 72.50%; Al2O3: 8.93%; Li2O: 10.33%; ZrO2: 3.08%; P2O5: 2.13%; B2O3: 0.86%; Na2O: 2.17%. It should be understood that the composition of the base glass used to prepare the microcrystalline glass substrate should be the same as the composition of the microcrystalline glass substrate, calculated by the mass percentage of oxides. Only the microcrystalline glass substrate of this composition is used in the following examples, but the composition of the microcrystalline glass substrate that can be used in the present invention is not limited to this component.

[0186] Comparative Example 1 is an ordinary glass substrate (i.e., Qinling glass), which comes from Chongqing Xinjing Special Glass Co., Ltd., and its raw material components are as follows, calculated by mass percentage: SiO2: 63.92%; Al2O3: 18.75%; Li2O: 4.44%; MgO: 4.31%; K2O: 2.72%; Na2O: 5.86%.

[0187] Comparative Example 2 is a microcrystalline glass substrate whose main crystal phases are zinc-magnesium spinel and zirconium oxide, which comes from Chongqing Xinjing Special Glass Co., Ltd. Its raw material components, calculated by mass percentage, are as follows: SiO2: 32.507%; Al2O3: 35.505%; ZrO2: 5.454%, MgO: 2.976%, ZnO: 10.318%, Na2O: 5.849%, B2O3: 5.131%, Ba2O: 2.260%.

[0188] The process for preparing the substrate glass of Examples 1-20 and Comparative Examples 1-2 of the present invention is as follows: each raw material is configured in a platinum crucible according to the formula of each Example 1-20 and Comparative Example 1-2, the total amount of the configured raw materials is 1000g, and then mixed with a V-type mixer for 30 minutes, and 5g of a clarifier NaCl is added after mixing, and then the raw materials are transferred to a platinum crucible, and then melted in a platinum crucible at 1650°C for 5 hours, and then poured into a molding mold preheated at 300°C (usually preheated to 200-400°C) for molding, cooled to 900°C, and then placed in a 500°C annealing furnace for annealing for 12 hours, and then cooled to room temperature with the furnace to obtain the substrate glass.

[0189] The process for preparing the microcrystalline glass substrate in Examples 1-20 of the present invention and Comparative Example 2 is as follows: the substrate glass obtained above is heat-treated in a resistance furnace (equipment model: SLX1400-40, manufacturer: Shanghai Shengli Testing Instrument Co., Ltd.), and the heat treatment process is carried out according to Table 1, and finally a microcrystalline glass sample brick is obtained. The microcrystalline glass sample brick is cut, CNC-processed (computer numerical control, i.e., CNC machine tool, the CNC equipment model used in the present invention is: RCG500S), and polished in sequence to obtain a microcrystalline glass substrate with a thickness of 0.64 mm.

[0190] The surface etching treatment process of embodiments 1-20 of the present invention is as follows: the microcrystalline glass substrate is cleaned with detergent, anhydrous ethanol and clean water in sequence, and the moisture on the two surfaces of the microcrystalline glass substrate is blown dry with a dust gun; then the treated microcrystalline glass substrate is placed in an etching solution for reaction for 180 minutes, and the reaction process is carried out in an ultrasonic cleaning machine and the etching solution temperature is kept at 25±2°C; after the reaction is completed, it is washed with clean water and dried with a dust gun to obtain the etched microcrystalline glass with a moth-eye structure. Among them, the etching solution used in the surface etching treatment is composed of the following raw materials in weight percentage: 0.1% hydrofluoric acid (the concentration of hydrofluoric acid is 40wt%), 4% barium sulfate, 1% cellulose, 1% silica sand, and 93.90% deionized water. Preparation method of etching solution: add barium sulfate, cellulose, and hydrofluoric acid with a concentration of 40wt% to deionized water at a stirring speed of 150r / min, stir and mix evenly, and the etching solution can be obtained.

[0191] In addition, the common glass substrate of comparative example 1 and the microcrystalline glass substrate of comparative example 2 whose main crystal phase is zinc magnesium spinel and zirconium oxide are etched by the same surface etching process as that of embodiment 1 of the present invention.

[0192] The examples 1-20 of the present invention and the comparative examples 1-2 were tested according to the performance test method described above; the performance test structures are shown in Table 2. The thickness of the glass substrates of the examples of the present invention and the comparative examples was 0.64 mm.

[0193] The microcrystalline glasses with moth-eye structures obtained after etching the microcrystalline glass substrates of Examples 1-20 of the present invention were subjected to AFM tests respectively. Three 7 μm*7 μm test surfaces were randomly selected for each example to obtain the A, B, h and L values ​​of the nanoscale protrusion structures of all test surfaces. The results are shown in Table 3; all satisfy the relationship (1) described in the present invention.

[0194] Table 1

[0195]

[0196]

[0197] Table 2

[0198]

[0199]

[0200] Table 3

[0201] serial number A(nm) B(nm) h(nm) L(nm) Example 1 15.5~41.4 14.8~37.4 5.48~35.14 0~155 Example 2 16.7~49.5 15.9~47.6 6.42~37.41 0~124 Example 3 15.9~47.2 14.7~46.2 7.02~38.65 0~104 Example 4 16.4~48.7 15.7~46.2 6.25~47.6 0~74.4 Example 5 17.5~46.4 16.2~43.4 6.41~56.7 0~73.2 Example 6 17.5~51.7 15.3~44.2 6.74~61.4 0~71.1 Example 7 18.5~62.8 18.0~57.4 6.75~73.2 0~67.4 Example 8 14.8~46.5 13.9~40.5 6.85~54.1 0~33.5 Example 9 17.2~49.5 16.8~49.1 6.31~58.7 0~35.4 Example 10 20.9~51.7 20.5~50.1 5.85~62.1 0~34.2 Embodiment 11 24.5~61.7 23.9~60.7 5.01~51.2 0~31.4 Example 12 12.8~62.5 11.8~57.7 4.85~35.2 0~131 Embodiment 13 17.8~51.2 17.5~50.6 5.24~37.5 0~114 Embodiment 14 15.6~59.4 14.3~55.7 4.85~45.6 0~95 Embodiment 15 22.9~55.4 21.8~52.0 6.74~43.66 0~76.5 Example 16 24.2~57.3 21.4~55.6 6.23~51.2 0~62.5 Embodiment 17 21.4~57.6 20.4~54.2 5.45~56.3 0~54.4 Embodiment 18 26.4~61.6 21.9~57.6 6.75~75.4 0~35.5 Embodiment 19 28.5~61.6 24.8~58.6 7.52~67.7 0~31.9 Embodiment 20 24.7~61.6 22.2~57.6 8.41~69.8 0~30.1

[0202] It can be seen from Example 2 and Comparative Examples 1-2 that the present invention uses a microcrystalline glass substrate whose main crystal phases are petalite and lithium silicate, and after surface etching with an etching solution, obtains a microcrystalline glass with a moth-eye structure having high transmittance in the visible light range.

[0203] By comparison Figure 6 and Figure 8 It can be seen that although Comparative Example 2 is a microcrystalline glass substrate with main crystal phases of zinc magnesium spinel and zirconium oxide crystals, this type of microcrystalline glass substrate does not form a moth-eye structure after etching, which indicates that not all microcrystalline glass substrates can form a moth-eye structure by etching; moreover, Figure 8 It can be seen that after the etching treatment, the crystal phase of the microcrystalline glass substrate of Comparative Example 2 that can be retained has a low degree of crystallinity and a small average grain size, which makes the retained crystal phase distribution very sparse, and does not bring an anti-reflection effect to Comparative Example 2. Instead, it greatly weakens the original transmittance of the microcrystalline glass substrate of Comparative Example 2.

[0204] The main crystalline phases of Examples 4 to 11 are petalite, lithium monosilicate, and lithium disilicate, with a crystallinity of 60.51 wt% to 94.72 wt%, an average grain size of 15.20 nm to 24.40 nm, and an initial transmittance TR of 0.64 mm at a wavelength of 550 nm. 550 is about 90%, and after etching, the glass-ceramics with moth-eye structure obtained in Examples 4 to 11 has a transmittance TR of 0.64 mm at a wavelength of 550 nm. 550 There was a significant increase, reaching more than 95%, ranging from 95.79% to 98.03%, which is significantly better than the transmittance of the microcrystalline glass before etching.

[0205] The main crystalline phases of Examples 15 to 20 are petalite and lithium disilicate, with a crystallinity of 60.81 wt% to 95.47 wt%, an average grain size of 17.4 nm to 25.10 nm, and an initial transmittance TR of 0.64 mm at a wavelength of 550 nm. 550 The transmittance is about 90%, and the highest transmittance is only 91.12%. After etching, the transmittance TR of the moth-eye-like glass-ceramics prepared in Examples 15 to 20 at a thickness of 0.64 mm under light at 550 nm is 550 There was a significant increase, reaching more than 96%, ranging from 96.25% to 98.87%, which is significantly better than the transmittance of microcrystalline glass before etching.

[0206] It can be seen from Table 3 that the surface nano-scale protrusion structure of the microcrystalline glass with a moth-eye-like structure obtained in Examples 1-20 of the present invention satisfies the relationship (1) described in the present invention in the spatial coordinate system; and the microcrystalline glass with a moth-eye-like structure has a high transmittance under light at 550nm when the thickness is 0.64mm.

[0207] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.

Claims

1. A display glass cover, characterized in that: It includes microcrystalline glass, which includes a microcrystalline glass substrate and a plurality of nanoscale protrusion structures arranged on the main surface of the microcrystalline glass substrate, and the plurality of nanoscale protrusion structures are integrated with the microcrystalline glass substrate, the nanoscale protrusion structures are crystalline substances of the microcrystalline glass, and the main crystalline phase of the microcrystalline glass substrate includes petalite and lithium silicate.

2. The display glass cover according to claim 1, characterized in that: The main crystalline phase of the microcrystalline glass includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate.

3. The display glass cover according to claim 1 or 2, characterized in that: The crystallinity of the microcrystalline glass substrate is greater than or equal to 30.00 wt %, and / or the average grain size of the microcrystalline glass substrate is 10.00 nm to 30.00 nm.

4. The display glass cover according to claim 1 or 2, characterized in that: The crystallinity of the microcrystalline glass substrate is 35.00 wt % to 95.00 wt %.

5. The display glass cover plate according to claim 1 or 2, characterized in that: The nano-scale protrusion structure is obtained by performing a surface etching process on the main surface of the microcrystalline glass substrate using an etching solution.

6. The display glass cover plate according to claim 5, characterized in that: The etching solution comprises the following components calculated by mass percentage: 0.01% to 16.00% of an acid solution, 0% to 18.00% of an additive, and the balance is water.

7. The display glass cover according to claim 6, characterized in that: The additives include one or more of barium sulfate, silica sand, and cellulose.

8. The display glass cover plate according to claim 1 or 2, characterized in that: It was measured on the surface of the nano-scale protrusion structure on the main surface that the transmittance of the microcrystalline glass at a wavelength of 550.00 nm was greater than or equal to 91.00% when the thickness was 0.64 mm.

9. The display glass cover according to claim 1 or 2, characterized in that: Calculated according to the mass percentage of oxides, the microcrystalline glass substrate includes the following components: SiO2: 70.00%-80.00%; Al2O3: 5.00%-10.00%; Li2O: 5.00%-15.00%; ZrO2: 0%-5.00%; P2O5: 0%-5.00%; B2O3: 0%-5.00%; Na2O: 0%-5.00%.

10. The display glass cover according to claim 1 or 2, characterized in that: The bottom surface of the nanoscale protrusion structure is elliptical, having a major axis A and a minor axis B. The height of the nanoscale protrusion structure in the vertical direction is h, and the nanoscale protrusion structure satisfies the following relationship in the spatial coordinate system (x1, y1, z1): Formula (1) takes the center point of the major axis A and the minor axis B as the origin, A = B or A ≠ B; x1 is the variable along the major axis A, y1 is the variable along the minor axis B, z1 is the variable along the height h, and 0<|x1|<A / 2, 0<|y1|<B / 2, 0<z1.

11. The display glass cover plate according to claim 10, characterized in that: The range of the major axis A of the bottom surface of the nanoscale protrusion structure is 12.0nm~65.0nm, preferably 15.00nm~63.00nm, preferably 16.00nm~60.00nm; the range of the minor axis B of the bottom surface of the nanoscale protrusion structure is 10.0nm~63.0nm, preferably 11.00nm~61.0nm, preferably 13.00nm~60.00nm, more preferably 14.70nm~60.00nm; the range of the height h of the nanoscale protrusion structure in the vertical direction is 4.50nm~76.00nm, preferably 4.85nm~75.40nm, preferably 5.00nm~70.00nm, and more preferably 6.00nm~70.00nm.

12. A glass-ceramic, characterized in that: It includes a microcrystalline glass substrate and a plurality of nanoscale protruding structures arranged on the main surface of the microcrystalline glass substrate, and the plurality of nanoscale protruding structures are integrated with the microcrystalline glass substrate; the nanoscale protruding structures are crystalline substances of microcrystalline glass, and the main crystalline phase of the microcrystalline glass substrate includes petalite and lithium silicate.

13. The glass-ceramic according to claim 12, characterized in that: The main crystalline phase of the microcrystalline glass includes petalite, lithium monosilicate and lithium disilicate, or the main crystalline phase includes petalite and lithium disilicate.

14. The glass-ceramics according to claim 12 or 13, characterized in that: Calculated according to the mass percentage of oxides, the microcrystalline glass substrate includes the following components: SiO2: 70.00%-80.00%; Al2O3: 5.00%-10.00%; Li2O: 5.00%-15.00%; ZrO2: 0%-5.00%; P2O5: 0%-5.00%; B2O3: 0%-5.00%; Na2O: 0%-5.00%.